Predictors of long‐term renal allograft survival after second kidney transplantation. Issue 8 (14th June 2020) - O'Kelly, John A.; Davis, Niall F.; Ferede, Atakelet A.; Breen, Kieran J.; O'Kelly, Patrick; MacCraith, Eoin; Forde, James; Mohan, Ponnusamy; Power, Richard; Smyth, Gordon; Little, Dilly M.
Abstract: Introduction: Few studies investigate significant perioperative predictors for long‐term renal allograft survival after second kidney transplant (SKT). We compared long‐term survival following SKT with primary kidney transplant and determined predictors of renal allograft failure after SKT. Methods: Outcomes of all primary or second kidney transplant recipients at a national kidney transplant center between 1993 and 2017 were reviewed. The primary outcomes measurements were renal allograft survival for both first and second kidney transplants. Secondary outcome measurements were incidence of delayed graft function (DGF), incidence of acute rejection (AR), and predictors for renal allograft survival in SKT recipients. Results: In total, there were 392 SKTs and 2748 primary kidney transplants performed between 1993 and 2017. The 1‐, 5‐, and 10‐year death‐censored graft survival for deceased‐donor recipients was 95.3%, 88.7%, and 78.2% for primary kidney transplant and 94.9%, 87.1%, and 74.9% for SKT ( P = .0288). Survival of primary renal allograft <6 years (HR 0.6, P = .017), AR episodes (HR 1.6, P = .031), DGF (HR 2.0, P = .005), and HLA‐DR MM (HR 1.7, P = .018) was independent predictors of long‐term renal allograft failure after SKT. Conclusion: These findings may provide important information on long‐term survival outcomes after SKT and for identifying patients at risk for long‐term renal allograft failure after SKT.